2005
DOI: 10.3354/meps295229
|View full text |Cite
|
Sign up to set email alerts
|

Ocean surgeonfish Acanthurus bahianus. I. The geography of demography

Abstract: The ocean surgeonfish Acanthurus bahianus is a common inhabitant of reefs throughout the west and central Atlantic. We examined geographic variation in its demography among 10 locations spanning 56°of latitude. These populations exhibit a great diversity of growth trajectories, as well as 3-fold variation in terminal size and maximum longevity. There are strongly contrasting patterns of habitat variation in demography at 2 sites: at Bermuda, fish settle inshore, grow to about asymptotic size and then, when 2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
110
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 40 publications
8
110
0
1
Order By: Relevance
“…Effects on longevity and survivorship: Robertson et al (2005) found inverse linear relationships between mean sea temperature and both maximum longevity and annual survivorship across 10 locations. They suggested that this pattern is related to a decline in mortality costs of reproduction with increasing latitude.…”
Section: Sampling Locationsmentioning
confidence: 94%
See 4 more Smart Citations
“…Effects on longevity and survivorship: Robertson et al (2005) found inverse linear relationships between mean sea temperature and both maximum longevity and annual survivorship across 10 locations. They suggested that this pattern is related to a decline in mortality costs of reproduction with increasing latitude.…”
Section: Sampling Locationsmentioning
confidence: 94%
“…Maximum size, which is a good proxy for asymptotic size, is directly related to mean sea temperature at the 10 locations where we made population samples (Robertson et al 2005). We expected that, if fishing affects size in Acanthurus bahianus, then maximum size at locations with heavy trap-fishing would be less than the size predicted from the size-temperature relationship at locations where there is little or no such fishing.…”
Section: Sampling Locationsmentioning
confidence: 97%
See 3 more Smart Citations